1998
DOI: 10.1111/j.1468-2885.1998.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

The Trials and Tribulations of Racialized Critical Rhetorical Theory: Understanding the Rhetorical Ambiguities of Proposition 187

Abstract: This essay explores the role that race plays in rhetorical theorizing. Linking the literature in critical race theory (CRT), critical rhetoric, and vernacular criticism, the essay examines the case of Proposition 187 for the ways in which race was deployed and occluded. The essay demonstrates that rhetoricians can and should systematically assess racial dimensions in communicative practices. Such a rhetorical turn emphasizes race as part of historical, legal, political, and cultural discourses. The authors bui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Rhetorical researchers have examined immigration policy messages across time and political contexts (Beasley, 2004(Beasley, , 2006Chavez, 2001;Cisneros, 2008;Demo, 2005Demo, , 2007Dorsey & Harlow, 2003;Flores, 2003;Hasian & Delgado, 1998;Mehan, 1997;Ono & Sloop, 2002;Santa Ana, 2002); and, in doing so, they have greatly expanded our understanding of the rhetorical process that drives U.S. immigration policy. Departing from this previous work, our project makes use of immigration policy texts as a way to resolve a tension between theories of gender-associated styles and moral frames.…”
Section: Textual Analysis: the 2007 Immigration Reform Debatementioning
confidence: 97%
See 1 more Smart Citation
“…Rhetorical researchers have examined immigration policy messages across time and political contexts (Beasley, 2004(Beasley, , 2006Chavez, 2001;Cisneros, 2008;Demo, 2005Demo, , 2007Dorsey & Harlow, 2003;Flores, 2003;Hasian & Delgado, 1998;Mehan, 1997;Ono & Sloop, 2002;Santa Ana, 2002); and, in doing so, they have greatly expanded our understanding of the rhetorical process that drives U.S. immigration policy. Departing from this previous work, our project makes use of immigration policy texts as a way to resolve a tension between theories of gender-associated styles and moral frames.…”
Section: Textual Analysis: the 2007 Immigration Reform Debatementioning
confidence: 97%
“…Her rhetoric even called into question whether immigrants would ever be able to cross over that line. When it comes to immigration policy, rhetoric has a history of drawing stark boundaries between Americans and immigrants residing on American soil (Beasley, 2004;Chavez, 2001;Cisneros, 2008;Hasian & Delgado, 1998;Mehan, 1997;Ono & Sloop, 2002). In her examination of over one century of presidential immigration rhetoric, Beasley (2004) observed that this discourse draws ''clear distinctions between 'immigrant' and 'American',between 'them' and 'us' '' (p. 90).…”
Section: Explaining the Masculine Style's Rhetorical Dominancementioning
confidence: 98%
“…Each has been critically examined for their racial and xenophobic dimensions and persuasive elements by scholars (Hasian & Delgado, 1998;Mukerjee, 2000;Ono & Sloop, 2002). Research during the '90s also brings into sharp focus the complexity embedded in producing critical inquiries about Latina/os.…”
Section: Decade Of (Re)turn -1990smentioning
confidence: 99%
“…Whereas other scholarly work in this area has emphasized the English-language discourse in this case alone, we actively integrate Spanish language and other "vernacular" commentaries for a more complete representation of this debate. Here we join those communication scholars who are interested in integrating vernacular voices of those who participate in salient social discussions (e.g., Hasian & Delgado, 1998;Ono & Sloop, 1995, as well as scholars who are interested in giving voice to "the other" (e.g., Flores, 1996;Orbe & Strother, 1996). Likewise, we seek to contribute to critical scholarship that articulates vernacular discourses to Latino/a communication studies (Holling, 2006, Calafell & Delgado, 2004, Delgado, 1998a, 1998bFlores & Hasian, 1997) and which further contributes to the growing body of Latino/a communication studies (Calafell, 2004;Guzmán & Valdivia, 2004;Mayer, 2004;Rojas, 2004;Valdivia, 2004;Zazueta Martínez, 2004).…”
mentioning
confidence: 99%